2022
DOI: 10.3389/fimmu.2022.947359
|View full text |Cite
|
Sign up to set email alerts
|

Divergent dynamics of inflammatory mediators and multiplex PCRs during airway infection in cystic fibrosis patients and healthy controls: Serial upper airway sampling by nasal lavage

Abstract: BackgroundIn cystic fibrosis (CF), acute respiratory exacerbations critically enhance pulmonary destruction. Since these mainly occur outside regular appointments, they remain unexplored. We previously elaborated a protocol for home-based upper airway (UAW) sampling obtaining nasal-lavage fluid (NLF), which, in contrast to sputum, does not require immediate processing. The aim of this study was to compare UAW inflammation and pathogen colonization during stable phases and exacerbations in CF patients and healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 67 publications
0
4
1
Order By: Relevance
“…In 95.5% of our patients, IL-17 A, [20]. This study showed values below 400 pg/ml for IL-6, which are on average higher than IL-6 measured in NL [8,18,20].…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations
“…In 95.5% of our patients, IL-17 A, [20]. This study showed values below 400 pg/ml for IL-6, which are on average higher than IL-6 measured in NL [8,18,20].…”
Section: Discussioncontrasting
confidence: 51%
“…Another study by Mulvanny et al used a Milliplex MAP Human High Sensitivity T-Cell Panel and analyzed cytokines in sputum samples in patients with stable chronic obstructive pulmonary disease (COPD) [ 20 ]. This study showed values below 400 pg/ml for IL-6, which are on average higher than IL-6 measured in NL [ 8 , 18 , 20 ].…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…The interpretation of the results achieved using different sampling methods is not yet clear. For instance, the use of new biomarkers is currently being investigated for better recognition of infection [21,22]. Furthermore, our cohort was not only limited to patients with respiratory infection symptoms but also included some with chest pain or poor general condition, which presumably also reduced the proportion of positive results.…”
Section: Discussionmentioning
confidence: 99%